2018
DOI: 10.2136/vzj2018.03.0047
|View full text |Cite
|
Sign up to set email alerts
|

Filtering of Period Infiltration in a Layered Vadose Zone: 1. Approximation of Damping and Time Lags

Abstract: Citation: Dickinson, J.E., and T.P.A. Ferré. 2018. Filtering of period infiltration in a layered vadose zone: 1. Approximation of damping and time lags. Vadose Zone J. 17:180047.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Specifically, we examine how the damping and time lags can accumulate as periodic forcings are transmitted through sequences of soil layers to conceptualize these responses at any depth. Dickinson and Ferré (2018) demonstrated that the approximate solution generally overpredicts these responses but provides the conditions in which the error in the responses is relatively small. Here we identify areas in a model that can be treated as having steady recharge or cyclical recharge with no significant time delays by using the approximate solution.…”
Section: Overview Of Approximate Solutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, we examine how the damping and time lags can accumulate as periodic forcings are transmitted through sequences of soil layers to conceptualize these responses at any depth. Dickinson and Ferré (2018) demonstrated that the approximate solution generally overpredicts these responses but provides the conditions in which the error in the responses is relatively small. Here we identify areas in a model that can be treated as having steady recharge or cyclical recharge with no significant time delays by using the approximate solution.…”
Section: Overview Of Approximate Solutionmentioning
confidence: 99%
“…Thus, the damping and time lag were likely to be accurate in the northern areas and for shorter infiltration cycles. The evaluation of the damping depth (Dickinson and Ferré, 2018, Fig. 7) provides insight into the accuracy of the damping maps.…”
Section: Application To Central Valley Californiamentioning
confidence: 99%
See 3 more Smart Citations